The Philosophy of Multicultural Education as a Foundation for Strengthening the Literacy and Identity of Banda Neira Children - Yuliati, Ni Komang Dwi Eka; Tika, I Nyoman; Suastra, Wayan; Atmaja, Ananta Wikrama Tungga (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Banda Neira has a central role in the birth of Indonesia as a country with the motto of Bhineka Tunggal ika. Banda Neira is often positioned as the